Miocene semidiurnal tidal rhythmites in Madre de Dios, Peru - Hovikoski, Jussi (2005)
New data from upper Miocene deposits in the Madre de Dios region, southern Peru, allow the delineation of tidal regime for the first time in western Amazonia and provide strong evidence of elevated tidal range and brackish-water influence. The results point out the insufficiency of the current depositional models and support the earlier hypothesis that western Amazonia was also connected to the Paranan Sea during the late Miocene. In this paper we present sedimentological, ichnological, and statistical (Fourier transformation) data from two selected outcrops containing rhythmite successions from an area that is traditionally considered as continental. The sediments are interpreted to represent tide-dominated, inner-middle estuarine deposits. The cyclic rhythmites display semidiurnal cyclicity. The results are significant because (1) they contradict recent interpretations of the area's paleoenvironmental history; (2) the evidence for tidal processes is persuasive; and (3) the delineated tidal regime and range provide a unique insight into the depositional dynamics of a system having many important paleogeographic implications.